Sokolství a olympismus [Sokol philosophy and olympism] - Martin Černek (Palacký University Olomouc, 2008)
Hlavní myšlenkou následujícího sdělení je stručné srovnání dvou myšlenkových koncepcí, sokolství a olympismu. Toto srovnání má poskytnout stručný přehled o myšlenkové koncepci sokolské filozofie, která provází českou společnost daleko předtím, než vznikl samostatný československý stát, a také dlouho před tím, než se podařilo obnovit novodobé olympijské hry. Pozornost je kladena na analýzu sokolské filozofie, která se v mnohém shoduje s myšlenkovou koncepcí novodobého olympismu. Nutno však říci, že hlavně v současnosti může být sokolská filozofie určitým myšlenkových východiskem pro situaci, kterou sociologové nazývají 'krizí olympismu'. [The Sokol philosophy as a typically Czech socio-cultural phenomenon is, not only from the point of view of its main thought, essentially adherent to the Olympism idea and movement, but we also find here stimuli, resources, ways of relating and standards, which preceded modern Olympism. Sokol is a philosophy which has been presented and still presents itself to us via the Czech Sokol Society (COS). The Sokol idea is based on the general national profile of citizens, their culture, identity, quality and ideals. Sokol is a way to perceive and comprehend the world and focuses on being human in the ontological sense of the word. The problem of responsibility arises, as it does with the bringing into reality of every great idea. If Sokol is responsible for the national moral profile of citizens, then Olympism is responsible for the nations as a complex. Responsibility in the sense of a whole can be expressed using the Greek term Areté. Basically the goal is, through training the human body, to achieve a state of harmony with the human soul. To be wholly responsible in the sense of self-overlapping to achieve a whole. Old Greek expressed this harmony as Kalokagathia. Sokol and Olympism are, in principle, forms of Areté. That is why we are concerned with that whole and fill it with such a content as to return it to its original position of esteem and respect - Areté.]